Administrative Law Mentoring Integrated with Digital Public Service Literacy for Community Empowerment: A Community Service Program in Kedaton District, Bandar Lampung City - Daffa Naufal Awanda Putra (Jurnal Pengabdian IPTEK, 2026)
Indonesia’s digital public services are expanding rapidly, yet many citizens still experience administrative exclusion because platform navigation requires both digital competence and procedural legal understanding. This community service program implemented administrative law mentoring integrated with digital public service literacy to strengthen community capacity in Kedaton District, Bandar Lampung City. The program targeted three recurring citizen pain points: population administration services, social assistance data governance, and complaint handling mechanisms using SP4N–LAPOR. A participatory method combined case-based legal mentoring, platform simulation, and guided practice, supported by simplified procedural maps and complaint drafting templates. Data were collected using baseline surveys, structured observation logs during mentoring, and post-program assessments two weeks after implementation. Nationally, Ombudsman RI reported receiving 10,846 public service complaints in 2024, up from 8,452 in 2023, showing a sustained problem of service access and maladministration in everyday administrative life (Ombudsman RI, 2025a; Ombudsman RI, 2025b; Antara, 2025) [1], [11], [12]. Program evaluation results show measurable improvements in participants’ administrative-rights knowledge, independent platform use, and confidence interacting with public institutions. The novelty lies in treating administrative law not as abstract doctrine but as “applied procedural science” embedded in digital workflows, thereby connecting legal norms, platform behavior, and citizen agency within real service encounters.